Shrinking towns and unoccupied housing: A new phenomenon and the future trend — not only in Eastern Germany - Bullinger, Dieter (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
Over the next 10 to 15 years, the towns and cities of Germany — and indeed throughout Europe — will feel the full impact of overall population decline. At present the effects of this new megatrend in urban development are most clearly evident in the towns of eastern Germany, which are suffering not only from the effects of natural negative population development, but are also experiencing serious population depletion through outward migration. The result is unoccupied housing, with major consequences both for the economy and for settlement structure. The author outlines possible measures and conflicts associated with managing urban shrinkage processes.
Keywords: Article